2020
DOI: 10.1177/1356389020905322
|View full text |Cite
|
Sign up to set email alerts
|

Applying Big Data visualization to detect trends in 30 years of performance reports

Abstract: Evaluators worldwide are dealing with a growing amount of unstructured electronic data, predominantly in textual format. Currently, evaluators analyze textual Big Data primarily using traditional content analysis methods based on keyword search, a practice that is limited to iterating over predefined concepts. But what if evaluators cannot define the necessary keywords for their analysis? Often we should examine trends in the way certain organizations have been operating, while our raw data are gigabytes of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Presumably to remedy this state of affairs, scholars have advanced three related threads: Some have outlined arguments for why it is important to integrate AI in evaluation (Bamberger, 2016; Hejnowicz & Chaplowe, 2021; Leeuw, 2020; York & Bamberger, 2020). Examples of potential uses of techniques grounded in one of AI's branches are being published, which offer case examples from which evaluation pracitioners can learn (see, e.g., Cintron & Montrosse‐Moorhead, 2021; Raveh et al., 2020; Roy & Rambo‐Hernandez, 2021). Others have highlighted critical questions about the use of AI in evaluation (Leeuw, 2020; Picciotto, 2020).…”
Section: The Importance Of Evaluative Criteria For Artificial Intelli...mentioning
confidence: 99%
“…Presumably to remedy this state of affairs, scholars have advanced three related threads: Some have outlined arguments for why it is important to integrate AI in evaluation (Bamberger, 2016; Hejnowicz & Chaplowe, 2021; Leeuw, 2020; York & Bamberger, 2020). Examples of potential uses of techniques grounded in one of AI's branches are being published, which offer case examples from which evaluation pracitioners can learn (see, e.g., Cintron & Montrosse‐Moorhead, 2021; Raveh et al., 2020; Roy & Rambo‐Hernandez, 2021). Others have highlighted critical questions about the use of AI in evaluation (Leeuw, 2020; Picciotto, 2020).…”
Section: The Importance Of Evaluative Criteria For Artificial Intelli...mentioning
confidence: 99%
“…However, some of these assumptions are not accurate and are not supported by massive data inputs [33,34]. Current well-documented theoretical studies have shown that data generated from various industry sectors, when fully applied, will significantly improve management effectiveness and economic performance [35,36]. NAR artificial neural networks, with easily adjustable parameters, can provide demand forecasting with high accuracy and with improved NSGA-III based on the good points set theory, resulting in a highly responsive space allocation strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Charitopoulos et al point out that the SVD rank reduction algorithm does not guarantee the nonnegativity of the matrix decomposition, so nonnegative matrix factorization (NMF) becomes a sensible choice for decomposing the PPMI, which guarantees the nonnegativity of the dimensional approximate reduction of the semantic relationship of the word-context information and is more consistent with the semantic relationship hypothesis [7]. Raveh et al demonstrated that matrix factorization methods are consistent with the word vectors of neural network language models in terms of task performance, such that PPMI-SVD matrix decomposition is equivalent to skipgram (SGNS) based on negative sampling [8]. The neural network language model has an inherent advantage over factorization methods, which have more flexible super parameter settings [9].…”
Section: Current Status Of Researchmentioning
confidence: 99%